Efficiency of cages with bioclimatic chamber in backyard guinea pig (Cavia porcellus) breeding at family level - Torres Salazar, Rober (2023)
The objective of the research was to evaluate the efficiency of bioclimatic chamber cages in backyard guinea pig raising at the family level. It was installed under a randomized complete block design, with two treatments and 4 families (blocks) in the locality of Taquia, Chachapoyas. Cages of 1.0 x 1.5 m were built, and a bioclimatic chamber of 0.61 x 1.0 m was placed inside them. The conventional cages were placed in a backyard tendal, without wall protection. The average temperature with the bioclimatic chamber was 18.077ºC and the ambient temperature was 13.65ºC. It was found that the number of offspring per breeder showed a highly significant difference, carried out by the JCCB system, with an average of 3.51 offspring per breeder. This was similar to the average weight of the offspring at birth, which was higher in the JCCB system (154.66 g). Similarly, the weaning weight of the offspring at weaning was also 1.3 times higher than the conventional system. Calf mortality at birth, with the CCCB system reached 1.75 % and the conventional system 3.75 %. In this sense, the technical breeding system for guinea pigs could generate possibilities for the quality of life of many rural families in the Amazonregion.